Application of human cardiac organoids in cardiovascular disease research - Zhang, Hongyan; Qu, Peng; Liu, Jun; Cheng, Panke; Lei, Qian (Frontiers in Cell and Developmental Biology, 2025)
With the progression of cardiovascular disease (CVD) treatment technologies, conventional animal models face limitations in clinical translation due to interspecies variations. Recently, human cardiac organoids (hCOs) have emerged as an innovative platform for CVD research. This review provides a comprehensive overview of the definition, characteristics, classifications, application and development of hCOs. Furthermore, this review examines the application of hCOs in models of myocardial infarction, heart failure, arrhythmias, and congenital heart diseases, highlighting their significance in replicating disease mechanisms and pathophysiological processes. It also explores their potential utility in drug screening and the development of therapeutic strategies. Although challenges persist regarding technical complexity and the standardization of models, the integration of multi-omics and artificial intelligence (AI) technologies offers a promising avenue for the clinical translation of hCOs.